1998
DOI: 10.1093/ajcn/67.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Diet, antioxidant status, and smoking habits in French men

Abstract: The aim of this study was to assess the association between smoking, food consumption, and antioxidant vitamin intake and plasma indexes of oxidative stress and antioxidant defenses in French adults. Food and nutrient intakes of 459 healthy men aged 23-57 y were estimated by the diet history method and analyzed by smoking status. Plasma alpha-tocopherol, ascorbic acid, and carotenoids were measured as antioxidants and malondialdehyde, protein Schiff bases, and autoantibodies against malondialdehyde-protein add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
106
1
5

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(122 citation statements)
references
References 55 publications
10
106
1
5
Order By: Relevance
“…Lower plasma ascorbic acid concentrations have been described in smokers than in nonsmokers of both sexes (Schectman et al, 1989;Mezzeti et al, 1995;Ross et al, 1995;Marangon et al, 1998;Lykkesfeldt et al, 2000;Wei et al, 2001;Dietrich et al, 2003). Smokers had also lower plasma b-carotene concentrations than did the nonsmokers (Byers & Guerrero, 1995;Stryker et al, 1988;Nierenberg et al, 1991;Marangon et al, 1998;Dietrich et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Lower plasma ascorbic acid concentrations have been described in smokers than in nonsmokers of both sexes (Schectman et al, 1989;Mezzeti et al, 1995;Ross et al, 1995;Marangon et al, 1998;Lykkesfeldt et al, 2000;Wei et al, 2001;Dietrich et al, 2003). Smokers had also lower plasma b-carotene concentrations than did the nonsmokers (Byers & Guerrero, 1995;Stryker et al, 1988;Nierenberg et al, 1991;Marangon et al, 1998;Dietrich et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Lower plasma ascorbic acid concentrations have been described in smokers than in nonsmokers of both sexes (Schectman et al, 1989;Mezzeti et al, 1995;Ross et al, 1995;Marangon et al, 1998;Lykkesfeldt et al, 2000;Wei et al, 2001;Dietrich et al, 2003). Smokers had also lower plasma b-carotene concentrations than did the nonsmokers (Byers & Guerrero, 1995;Stryker et al, 1988;Nierenberg et al, 1991;Marangon et al, 1998;Dietrich et al, 2003). The abundance of free radicals in, or produced by, cigarette smoke may induce an oxidative stress on both the respiratory and circulatory systems (Pryor & Stone, 1993;Eiserich et al, 1995), and the lower levels of antioxidants found in smokers may partly be a consequence of a greater antioxidant depletion due to a sustained smoke-related oxidant load (Mezzeti et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exposures that precede the onset of disease are routinely evaluated with retrospectively administered interviews or questionnaires, as evidenced by epidemiologic studies that Ž evaluate exposures with dietary histories Goodman et al, . 1997;Slattery et al, 1997;Marangon et al, 1998 , smok-Ž ing histories Doll and Hill, 1950;Hirayama, 1981;Tri-. chopoulos et al, 1981 , dose reconstruction for exposure to Ž ionizing radiation Stevens et al, 1990;Kerber et al, .…”
Section: Introductionmentioning
confidence: 99%